ANALISIS TINGKAT KESEHATAN KOPERASI UNIT DESA “MELATI” DI DESA EMPAT BALAI KECAMATAN KUOK BERDASARKAN PERATURAN MENTERI KOPERASI DAN USAHA KECIL DAN MENENGAH REPUBLIK INDONESIA NOMOR. 14/PER/M.KUKM/XII/2009 - Suci Rahmadani; Sri Kartikowati; RM Riadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract; The purpose this paper is to know the level of health of Koperasi Unit Desa Melati based on the Minister of Cooperatives and Small and Medium business, No. 14 / M.KUKM / XII / 2009. The research was conducted at Koperasi Unit Desa Melati in the village Empat Balai District of Kuok. This study started in April 2015. This is quantitative descriptive research.The research result showed that; in 2010 the acquisition of the cooperative health level score was 51.25 to predicate less healthy. In 2011 the acquisition of the rating of the cooperative is to predicate less healthy 48.25. In 2012 the acquisition of the rating of the savings and loan is 48.50 with the predicate less healthy. In 2013 the acquisition of the rating of the cooperative is to predicate less healthy 48.25. In 2014 the acquisition of the cooperative health level assessment score was 48.75 with the predicate less healthy.Keywords: financial statements, the acquisition of the cooperative health level